Conhecimento tecnológico e inovação no Brasil: Um estudo patentométrico na universidade estadual paulista - Pavanelli, Maria Aparecida [UNESP]; Oliveira, Ely Francina Tannuri de [UNESP] (My University, 2012)
The patent recordings of the Universidade Estadual Paulista (UNESP) since its first recording in 1980 to December 2010 are analysed, in order to promote their visibility, and analyze their authors, most productive areas and most common themes. As research procedure, we verified the relation of all patents deposited, following different types: patent recordings of invention, utility models, brands and industrial drawings, all of which were obtained from the Unesp Innovation Agency. Finally, the scientific colaboration network among the researchers was drawn using PAJEK. The most productive authors are grouped in the Araraqua Chemistry Institute and the engeneering area.
Technological knowledge and innovation in Brazil: A patentometric study in the universidad estadual paulista
Keywords: Patentometrics; Patents; Technological innovation; Universidade estadual paulista (brasil)